A pH-responsive platform combining chemodynamic therapy with limotherapy for simultaneous bioimaging and synergistic cancer therapy. (September 2019) - Xiao, Jianmin; Zhang, Guilong; Xu, Rui; Chen, Hui; Wang, Huijuan; Tian, Geng; Wang, Bin; Yang, Chi; Bai, Guo; Zhang, Zhiyuan; Yang, Hongyi; Zhong, Kai; et al.
Abstract: Chemodynamic therapy (CDT) was widely exploited for cancer therapy and expected to replace traditional anticancer drug therapies. Generally, CDT needs to combine with extra therapeutic methods for obtaining the optimal therapeutic efficacy of cancer. Herein, a multifunctional theranostic platform combing CDT with limotherapy was developed via nanoselenium (nano-Se)-coated manganese carbonate-deposited iron oxide nanoparticle (MCDION-Se). MCDION-Se could release abundant of Mn 2+ ions that catalyzed H2 O2 into hydroxyl radicals (· OH) via a Fenton-like reaction, effectively inducing the apoptosis of cancer cells. Besides, nano-Se coated onto MCDION-Se also dramatically activated superoxide dismutase (SOD) and promoted the generation of superoxide anion radicals (SOARs) in tumor tissue. Subsequently, a high content of H2 O2 was produced via SOD catalysis of SOARs, further enhancing CDT efficiency. Meanwhile, the nano-Se and Mn 2+ ions inhibited the generation of adenosine triphosphate (ATP), thus starving cancer cells. In addition, in vitro and in vivo experiments showed that MCDION-Se could effectively enhance the contrast of tumor tissue and improve the quality of magnetic resonance imaging (MRI). Overall, this work provided a nanoplatform that combined CDT with limotherapy for cancer therapy and simultaneously utilized MRI for monitoring the treatment of tumors. Graphical abstract: A pH-responsive free-drug theranostic platform (MCDION-Se) combined chemodynamic therapy with limotherapy was developed for MRI-guided tumor therapy.Image 1